Genetic and morphological approach to reappraising species validity in two different Anagyrus wasps (Hymenoptera: Encyrtidae) attracted by cyclolavandulyl butyrate. Issue 2 (12th March 2020) - Sugawara, Yuma; Mita, Toshiharu; Tabata, Jun; Ueno, Takatoshi
Abstract: Members of the genus Anagyrus are primary endoparasitoids of mealybugs and thus include potentially important biological control agents of mealybug pests. We have previously discovered that an analogous compound of a mealybug pheromone, cyclolavandulyl butyrate (CLB), strongly attracts Anagyrus sawadai Ishii and can enhance the foraging activity of this wasp in CLB‐treated orchards. In the present study, we found two groups of Anagyrus parasitoids that differed in color were attracted to CLB. One was A. sawadai and the other type was morphologically identified as A . subalbipes Ishii, which had been considered to be synonymous with A. sawadai . We suspected these two color populations of Anagyrus must be independent species because of their different emergence patterns in the field. Our morphological and molecular analyses supported this idea. We confirmed morphologically diagnostic features to distinguish the two species. Furthermore, molecular phylogenetic analysis based on COI sequences revealed that A. sawadai and A . subalbipes were placed in entirely different clusters. These findings not only offered new insight into the taxonomy and phylogeny of Anagyrus spp. but also provided critical knowledge for the use of these indigenous natural enemies for biological control of mealybugs in agricultural fields. Abstract : In this manuscript, we re‐examined two Anagyrus species, which had been confused for many years, by molecular and morphometric approaches. We found the two parasitoids were good species and also new diagnostic characters applicable to identify many other cryptic species in Encyrtidae.